# Solve the equation 3y+6=y-2 for y.

changchengliang | Certified Educator

calendarEducator since 2010

starTop subject is Math

### 3y+6=y-2

We first try to group terms containing the unknown ("y" in this case) to one side of the equation and those that do not contain the unknown to the other side.

With that in mind, we have to abide by some rules pertaining to algebraic manipulation.  Simply put, the rule can be sum up as "what ever operation you do on one side, do it equally on the other"

First, we want to be able to move the y on the RHS (Right...

(The entire section contains 2 answers and 283 words.)

check Approved by eNotes Editorial

Tushar Chandra | Certified Educator

calendarEducator since 2010

starTop subjects are Math, Science, and Business

check Approved by eNotes Editorial

neela | Student

To solve 3y+6 = y-6.

This is a simple linear equation in one variable y.

To determine y,  we have to bring the equation to the form y = number.

To do this we  first subtract y from both sides:

3y+6 -y = y-6 -y. Then we get:

2y+6 = -6.

Now we subtract 6 from both sides:

2y+6-6 = -6-6. Then we get:

2y = -12

Now we divide both sides by 2 :

2y/2 = -12/2 and we get:

y = -6.

So y = -6 is the solution.